Non-clostridial gas gangrene of a diabetic foot with COVID-19 infection - Bakhshi, Girish D.; Patel, Owais Ahmed; Pawar, Dinesh; Shah, Jessicka (International Surgery Journal, 2020)
Gas gangrene is a manifestation of soft tissue infection by clostridial group of bacteria. Non-clostridial gas gangrene is uncommon and seen rarely in diabetics. In the era of COVID-19 pandemic where COVID-19 itself induces hyperglycemia non clostridial gas gangrene may arise due to altered immunity. We present a case of non clostridial gas gangrene of lower limb in a middle aged person who was not a known diabetic. A brief case report with review of literature is presented.